When disks collide: major and minor mergers in disk galaxies. Issue Volume 9:Issue S304(2013) (25th July 2014) - Mezcua, M.; Lobanov, A. P.; Mediavilla, E.; Karouzos, M.
Abstract: We present the surface brightness profile fitting of a sample of double nucleus disk galaxies, minor merger candidates. We have decomposed these systems into two compact nuclear components and one or two extended galaxy disk components and estimated the luminosity of the primary and secondary nucleus and of the host galaxy and the separation between the two nuclei. Based on the ratio of nuclear luminosities we find that most of the sources qualify as major mergers despite their initial classification as minor merging systems. This is supported by the finding that 65% of the host galaxies are fitted only by one galaxy disk and that the luminosity of both the primary and the secondary nucleus decreases with decreasing nuclear separation, as expected from simulations of disk galaxy mergers. All these results indicate that these sources are most plausibly in the post-merger state of a major merger event. We also identify 19 candidates to binary active nucleus with nuclear separation ≤1 kpc.